(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
During a recession, many firms favour a strategy of reducing the number of employees by restructuring their workforce. Focusing on the particular case of redundancy, this study will analyze the effect that downsizing has had on levels of profitability, efficiency and productivity, on the top five entities of the Spanish banking system/financial sector. With this in mind, the study uses the example of five organizations in the financial sector that are all listed on the IBEX 35 over a 10 year time span (2003-2012).